Faculty Equity Issues and Challenges: Analysis of Problems and Obstacles that Outstanding Engineering Faculty Face - Vedhathiri, Thanikachalam (Journal of Engineering Education Transformations, 2023)
Equity is defined as â€œfairness and impartiality based on even-handed treatmentâ€ (Nace, 2021, Unitedwaynce, 2021). Current engineering education problems are the improper selection of faculty members, educational leaders, and administrators. Equity approaches will alone sustain the fast growth of attributes of graduates, and service to society through creating human and knowledge capital. The National Education Policy 2020 focuses on the vibrant growth of engineering education. This research paper assesses the prevailing equity culture, getting feedback from the senior faculty members, and suggests ways and means of implementing equity, norms, and standards in recruiting outstanding and well-accomplished faculty members, and training and developing them. Best practices in ethics, areas that require major change and development, the impact of ethical practice, and the responsibilities of maintaining ethics in an institute are presented